ChemInform Abstract: Synthesis and Evaluation of Novel Azoles as Potent Antifungal Agents. Issue 17 (28th April 2014) - Li, Liangjing; Ding, Hao; Wang, Baogang; Yu, Shichong; Zou, Yan; Chai, Xiaoyun; Wu, Qiuye
Abstract All new azoles (III) (20 examples) show good antifungal activities against seven common clinical fungi, but are inactive against Aspergillus fumigatus.